Value of triple test in the diagnosis of palpable breast lump. - Joshi, Mukund Raj (2002)
ABSTRACT: Breast cancer is one of the major cancer in females and the most commonly diagnosed cancer in Nepal 1. The disease has to be suspected when one encounters a solid mass in the breast 2. One of the most common operations performed in outpatient surgical suites is biopsy of the breast. Public-awareness campaigns, news coverage of the frequency with which breast cancer is encountered, and instructional programs for self-examination of the breast have heightened awareness of the need for self-examination and the consequences of discovery of a mass in the breast. As recently as the early 1980s, any patient with a breast mass was subjected to an open biopsy. Unfortunately, the patients with fibrous dysplasia of the breast often have recurrence of breast masses, and it was not uncommon to encounter patients with several separate scars on or both breasts from that practice 3. Despite the advances in the management of breast cancer over the last several years, diagnosis of breast cancer still poses several problems; missed diagnosis, both false positives and negatives and the late diagnosis4 . The physical examination is still the first step in the breast cancer diagnosis, and it is the most widely used method2. Clinical examination and mammography, either alone or in combination, do not identify all malignant breast lesion, diagnostic accuracy has been reported to be 40% each for the patient below 50year5, although, the results are variable in different studies. Diagnostic accuracy of FNAC in diagnosing breast lump has been reported to over 90%6,7. The "Triple test" initially described in the mid 1970s is the evaluation of palpable breast masses by Physical examination, Mammography and the fine needle aspiration cytology 8. The triple test has proved a reliable tool for the accurate diagnosis of palpable breast masses, is technically simple, and results in substantially reduced expense and morbidity compared with open surgical biopsy. One large scale prospective trial and several smaller studies of triple test followed by selective confirmatory open biopsy found that concordant benign triple test results ( all 3 component interpreted as benign) correctly predicted the absence of malignancy, as determined either by histopathologic examination or clinical follow up 6,10,11',12,13,14. Present study conducted in surgical department of the Institute includes total of 52 cases subjected for triple assessment of palpable breast lump for evaluation of the accuracy of individual tests and combined tests.